2022
DOI: 10.1002/mco2.144
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial–mesenchymal transition: The history, regulatory mechanism, and cancer therapeutic opportunities

Abstract: Epithelial–mesenchymal transition (EMT) is a program wherein epithelial cells lose their junctions and polarity while acquiring mesenchymal properties and invasive ability. Originally defined as an embryogenesis event, EMT has been recognized as a crucial process in tumor progression. During EMT, cell–cell junctions and cell–matrix attachments are disrupted, and the cytoskeleton is remodeled to enhance mobility of cells. This transition of phenotype is largely driven by a group of key transcription factors, ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 549 publications
(1,151 reference statements)
0
45
0
2
Order By: Relevance
“…One of the conceivable effector mechanisms is the induction of epithelial-mesenchymal transformation (EMT), characterized by invasion and enhanced motility. 52 Indeed, abemaciclib triggered vimentin and N-cadherin expression, especially in Mlh1 −/− mice, but effectively suppressed Fpr2 , which is also involved in invasion and metastasis. 53 , 54 We, therefore, conclude a compensatory mechanism to counteract abemaciclib-driven EMT.…”
Section: Discussionmentioning
confidence: 96%
“…One of the conceivable effector mechanisms is the induction of epithelial-mesenchymal transformation (EMT), characterized by invasion and enhanced motility. 52 Indeed, abemaciclib triggered vimentin and N-cadherin expression, especially in Mlh1 −/− mice, but effectively suppressed Fpr2 , which is also involved in invasion and metastasis. 53 , 54 We, therefore, conclude a compensatory mechanism to counteract abemaciclib-driven EMT.…”
Section: Discussionmentioning
confidence: 96%
“…However, radioresistance is one of the main challenges for the applications of radiotherapy. At present, a series of studies have pointed out that radioresistance is related to DNA repair capacity, reduced apoptosis, cell cycle status, EMT and other factors, among which EMT is one of the most important factors affecting the sensitivity of cancer cells to ionizing radiation (IR) [39][40][41]. Studies have shown that IR-induced EMT accelerates the invasion, migration, and radioresistance of various tumor cell lines, including lung, liver, and breast cancer, after radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, radioresistance is one of the main challenges for the applications of radiotherapy. At present, a series of studies have pointed out that radioresistance is related to DNA repair capacity, reduced apoptosis, cell cycle status, EMT and other factors, among which EMT is one of the most important factors affecting the sensitivity of cancer cells to ionizing radiation (IR) [40][41][42]. Studies have shown that IR-induced EMT accelerates the invasion, migration, and radioresistance of various tumor cell lines including lung, liver, and breast cancer after radiotherapy.…”
Section: Discussionmentioning
confidence: 99%